Evaluation of the opinion of undergraduate students in the health area regarding people with mental disorders (Research, Society and Development, 2021)
Objective: To evaluate the opinion and attitudes of university students in the health area towards people with mental disorders. Materials and methods: Quantitative and cross-sectional research, with a descriptive approach, carried out with 328 undergraduate students at a Federal University in northeastern Brazil. The Opinions Scale on Mental Illness and a questionnaire to characterize the sociodemographic profile of the participants were used. Furthermore, for data analysis, the Kolmogorov-Smirnov, Mann-Whitney and Kruskal-Wallis tests were used. Results: The study found that Medicine was the course responsible for the lowest level of stigma and Dentistry, the one with the highest stigma. It was noticed that first-year students had a higher degree of stigma compared to students in the last years of graduation. This data was also prevalent among male individuals. Differences were observed in terms of gender, course, year of graduation, mental health discipline and contact with people with mental disorders. In the domains, statistical significance was obtained in all, although each strand correlated with a different group of categories. Conclusions: Stigma is one of the main barriers in caring for people with mental disorders. Thus, the association of theoretical content with internship practice during graduation is the main way to reduce it.